Analisis Proses Rekrutmen Dan Seleksi Terhadap Kinerja Karyawan Pada Radio Del FM (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research was conducted to find out how the Recruitment and Selection Process affects employee performance at Radio Del FM Laguboti, to find out obstacles and alternative solutions in solving problems. Data collection techniques are through observation and interviews, namely directly observing the object being studied and with documentation. Based on the results of the discussion, it shows that the Employee Recruitment and Selection process at Radio Del FM Laguboti is in accordance with the general standards of roles and authority as stated in the job description and has been effective in finding new employees needed by the company. company. The obstacles that occur are lack of focus at work, a backlog of work and work taking a long time to complete, this is because the capacity is insufficient if there is only one worker. The solutions implemented temporarily are still not effective because some alternatives are sometimes still disrupted by urgent work that must be prioritized. In developing an administration system in a company, although development is slow, to achieve good development, the support of many parties and focus in its development is very necessary.